2023
DOI: 10.1039/d2ta08598d
|View full text |Cite
|
Sign up to set email alerts
|

Structural engineering of metal–organic layers toward stable Li–CO2 batteries

Abstract: Rational design of metal organic layers (MOL) with well exposed catalytic sites and versatile structures holds great promise for boosting CO2 reduction/evolution kinetics in Li-CO2 batteries. In this work, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…After discharging, the newly emerging diffraction peak in the PXRD patterns of HOF-FJU-1-Ru@CNT can be clearly identified as Li 2 CO 3 (PDF#72-1216). [20] Furthermore, the disappearance of the Li 2 CO 3 diffraction peak after charging evidently illustrates the good reversibility of HOF-FJU-1-Ru@CNT as a cathodic catalyst for Li-CO 2 batteries (Figure 4a). Importantly, the positions of the characteristic peaks of HOF-FJU-1 remain unchanged even after a long period of cycling, implying good structural stability of HOF-FJU-1.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…After discharging, the newly emerging diffraction peak in the PXRD patterns of HOF-FJU-1-Ru@CNT can be clearly identified as Li 2 CO 3 (PDF#72-1216). [20] Furthermore, the disappearance of the Li 2 CO 3 diffraction peak after charging evidently illustrates the good reversibility of HOF-FJU-1-Ru@CNT as a cathodic catalyst for Li-CO 2 batteries (Figure 4a). Importantly, the positions of the characteristic peaks of HOF-FJU-1 remain unchanged even after a long period of cycling, implying good structural stability of HOF-FJU-1.…”
Section: Resultsmentioning
confidence: 89%
“…[17][18][19] Crystalline organic frameworks with well-defined porous network structures and multifunctional sites, including metal-organic frameworks (MOFs), covalent-organic frameworks (COFs), and hydrogen-bonded organic frameworks (HOFs), provide an ideal platform for the development of stable Li-CO 2 batteries. [20][21][22][23] For example, Wang et al [24] used Mn-MOF as a porous cathodic catalyst for the first time and showed that MOF with high CO 2 trapping capability can improve the electrochemical performance of batteries. This work has greatly promoted the application of crystalline organic framework materials in Li-CO 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As represented in Figure 4a, the battery‘s impedance increases significantly after discharging due to the formation of insulating Li 2 CO 3 on the surface of the cathode catalyst. After charging, despite a slight increase in the impedance compared to the original state, it has been significantly decreased when compared with the discharge state, indicating that most discharge products have been catalytically decomposed in the charging process [44,45] …”
Section: Resultsmentioning
confidence: 99%
“…After charging, despite a slight increase in the impedance compared to the original state, it has been significantly decreased when compared with the discharge state, indicating that most discharge products have been catalytically decomposed in the charging process. [44,45] To further understand the structural stability, electrochemical products during the discharge-charge process, and reaction mechanism of the cathode materials in the LiÀ CO 2 battery, the discharged and charged process RuNi/MWCNTs cathodes were disassembled from the LiÀ CO 2 battery for the XRD, XPS, and FESEM measurements.…”
Section: Investigation Of Electrodes or Post-characterizationmentioning
confidence: 99%
“…Organic framework materials such as covalent organic frameworks (COFs), metal organic frameworks (MOFs), and hydrogen-bonded organic frameworks (HOFs), due to their high porosity, tunable structure, and high specific surface area, have been widely used in gas adsorption/separation, catalysis, photoelectricity, , and energy fields. With excellent thermal stability and polymer compatibility, such organic framework material enables the construction of favorable polymer composites and theoretically improves the flame safety of polymers . Since the first case of MOFs was reported as FRs for polymers, the application of organic framework materials for flame retardancy of polymers has received extensive attention, for example, pore doping of MOFs or the construction of hollow MOF materials with different particle sizes to be used as FRs of polymers , and the development of triazine-based COFs or the construction of COF nanosheets to enhance the flame-retardant capability of polymers. , …”
Section: Introductionmentioning
confidence: 99%